2016
DOI: 10.1088/0957-4484/27/35/355703
|View full text |Cite
|
Sign up to set email alerts
|

Polarity dependent strongly inhomogeneous In-incorporation in GaN nanocolumns

Abstract: In this work, GaN/InGaN/GaN nanocolumns (NCs) have been grown by molecular beam epitaxy. Selective area growth (SAG) and self-organized growth (SOG) were performed simultaneously in patterned and unpatterned regions of the same substrate, respectively. The resulting structures show different tip morphologies and structural properties due to the different polarity along the growth direction, namely Ga-polar with r-plane faceted tips for the SAG NCs and N-polar with c-plane top facet for the SOG ones. When growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…The authors found the driving force for indium surface segregation to be stronger in the case of Ga-face polarity. Likewise, a strong polarity dependent inhomogeneous In-incorporation has been experimentally encountered in GaN nanocolumns grown by MBE . Although InGaN/GaN MQWs are also deposited on the n upper segment of the GaN wire, our findings suggest that In incorporation at the top of the structure seems to be easier on N-polar GaN (n ++ Si-doped segments) than on Ga-polar GaN, as reported by Nath et al., who provided experimental evidence of such effect in epitaxial layers.…”
supporting
confidence: 82%
“…The authors found the driving force for indium surface segregation to be stronger in the case of Ga-face polarity. Likewise, a strong polarity dependent inhomogeneous In-incorporation has been experimentally encountered in GaN nanocolumns grown by MBE . Although InGaN/GaN MQWs are also deposited on the n upper segment of the GaN wire, our findings suggest that In incorporation at the top of the structure seems to be easier on N-polar GaN (n ++ Si-doped segments) than on Ga-polar GaN, as reported by Nath et al., who provided experimental evidence of such effect in epitaxial layers.…”
supporting
confidence: 82%
“…Moreover, individual low-dimensional nanostructures such as nanosheets and nanobelts with a large area/thickness ratio can also be applied in fields such as spintronics and topological quantum computing . Additionally, it has been found that polarity plays a crucial role in the III–V nanowire growth, which can influence crystal quality, morphology, compositional distribution, and growth direction. Therefore, the polarity-driven effect can be a potential approach towards creating novel III–V nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of GaN structures have Ga-polar surfaces, N-polar surfaces offer a great advantage for high electron mobility transistors providing a strong back barrier layer, low resistivity Ohmic contacts and improved capability for large scale device processing . Recently there has been immense interest in determining polarity in semiconductor based nanowires in order to better understand their polarity dependent growth mechanisms. In some cases the polarity also determines the final shape of the nanowires and can also be engineered to form new nanostructures …”
mentioning
confidence: 99%